2013
DOI: 10.3389/fnint.2013.00059
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory process in Alzheimer's Disease

Abstract: Alzheimer Disease (AD) is a neurodegenerative disorder and the most common form of dementia. Histopathologically is characterized by the presence of two major hallmarks, the intracellular neurofibrillary tangles (NFTs) and extracellular neuritic plaques (NPs) surrounded by activated astrocytes and microglia. NFTs consist of paired helical filaments of truncated tau protein that is abnormally hyperphosphorylated. The main component in the NP is the amyloid-β peptide (Aβ), a small fragment of 40–42 amino acids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
245
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(279 citation statements)
references
References 175 publications
8
245
0
4
Order By: Relevance
“…103 Clustering of activated microglia and astrocytes have been reported surrounding A plaques and correlated with elevated inflammatory cytokines such as interleukin (IL)-1, IL-6, and tumor necrosis factor-. 104,105 Furthermore, peripheral monocytes/macrophages are capable of clearing vascular A . 106 In an in vivo multi-photon imaging study, circulating monocytes have been shown to enter luminal walls of A -positive veins and carry amyloid back into the bloodstream.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…103 Clustering of activated microglia and astrocytes have been reported surrounding A plaques and correlated with elevated inflammatory cytokines such as interleukin (IL)-1, IL-6, and tumor necrosis factor-. 104,105 Furthermore, peripheral monocytes/macrophages are capable of clearing vascular A . 106 In an in vivo multi-photon imaging study, circulating monocytes have been shown to enter luminal walls of A -positive veins and carry amyloid back into the bloodstream.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Increased levels in tauopathy in mouse model; this small glycoprotein was found elevated in CSF and plasma in AD subjects [38,49,50] FVII Involved in the coagulation cascade and required for thrombin generation, which has also been linked to AD [38] TARC Involved in the inflammatory response and the induction of cell migration; together with other proteins forms a biomarker profile that can distinguish AD versus controls [18] SAA High levels in plasma has been found in cardiovascular disease but the evidence for an association with cognitive decline is not clear [51] sICAM1 Has been found in amyloid plaques and others brain structures with low levels of amyloid beta deposits; peripheral role in AD [52] Adiponectin Modulates certain metabolic processes; may be related to changes in prodromal and early stage AD [38] IL-1β Proinflammatory cytokine overexpressed in AD brains near to amyloid plaques; higher blood concentrations were detected in AD subjects [44] MIP-1α Possesses inflammatory, pyrogenic and chemokinetic properties; probable involvement in microglial activation [53] AD: Alzheimer's disease; CJD: Creutzfeldt-Jakob disease; CSF: Cerebrospinal fluid; DLB: Dementia with Lewy bodies; PD: Parkinson's disease.…”
Section: I309mentioning
confidence: 99%
“…In addition, F03 has been reported as an anti-inflammatory agent [60][61][62]. As chronic inflammation may be a factor contributing to the onset of AD [63], this drug may be of even greater utility in the treatment or prevention of AD.Others are also identifying sAPPα enhancers. Lee et al, found that cilostazol attenuates Aβ production by increasing ADAM10 activity via SirT1-coupled Retinoic Acid Receptor-β (RARβ) activation in N2a cells expressing human APP Swedish (Swe) mutation [64].…”
mentioning
confidence: 99%